Heat Distribution on Abdominal Aorta Having Aneurysm During Hyperthermia Therapeutic - Asmuin, Norzelawati; Jun Xiong, Lee; Kamarudin, M. Saddam; Mohammad, Aswad; Taib, Ishkrizat (Research Progress in Mechanical and Manufacturing Engineering, 2020)
Hyperthermia therapy is an induce heat treatment to the tumour temperature elevated with temperature 40˚C - 43˚C to cure the cancerous tissues. Hyperthermia therapy uses an outer heat source to raise the temperature of the tumour to 40 ˚C -43°C for a certain period. On the other hand, abdominal aortic aneurysm is an enlargement area of an abdominal aorta. Over time, blood flow can cause a weak area to bulge like a balloon. An abdominal aortic aneurysm (AAA) occurs in the abdominal section of the aorta. Nowadays, the common treatment for AAA is open surgery and endovascular aortic repair (EVAR). There is two treatment for abdominal aortic aneurysm nowadays, the potential for risk is high to cause death and post-procedural complications. However, an alternative way to replace the open surgery and endovascular aortic repair (EVAR) was found, it called a non-invasive method. Hyperthermia therapy with an outer heat source is an alternative idea for treatment AAA. In this study, a heat source with 4 different temperature was used to raise the temperature of the AAA area and two difference physiological condition was applied in the abdominal aorta. The 4-difference temperature of heat source is 50˚C, 55˚C, 60˚C, 65°C and the two physiological condition are normal blood pressure (85mmHg) and high blood pressure (140mmHg). In this pilot study was focus on temperature distribution at the abdominal aorta wall. Computational fluid dynamic (CFD) used in this study to simulate the heat distribution on the abdominal aorta wall. CFD software used in this study is ANSYS version R19.2. In this study, the result shows that the heat source at temperature 50˚C - 60°C, the normal abdominal aorta wall and abdominal aorta having aneurysm wall temperature reach 39˚C - 44°C in NBP and HBP condition respectively.